1994
DOI: 10.1007/bf02354427
|View full text |Cite
|
Sign up to set email alerts
|

Cold floor effects on homicide

Abstract: The cold floor pattern (a lack of homicides on days with extremely cold temperatures that was found by Cheatwood in Baltimore) is to be expected by chance. Under a model in which the number of homicides and the maximum temperature are independent, the probability that a day will fall below the cold floor is small. The Baltimore data do not support a model in which extremely cold weather suppresses human aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Studies that examined cold floor effects on crime suggested a significant influence of warm weather on interpersonal violent crimes (Cheatwood, 1995;Cohn, 1990aCohn, , 1996Loftin & Cheatwood, 1996). Rotton and Cohn (2000a) examined the effects of the weather on assault and disorderly conduct and found a significant impact of the weather on assault.…”
Section: Literature and Theoretical Reviewmentioning
confidence: 97%
“…Studies that examined cold floor effects on crime suggested a significant influence of warm weather on interpersonal violent crimes (Cheatwood, 1995;Cohn, 1990aCohn, , 1996Loftin & Cheatwood, 1996). Rotton and Cohn (2000a) examined the effects of the weather on assault and disorderly conduct and found a significant impact of the weather on assault.…”
Section: Literature and Theoretical Reviewmentioning
confidence: 97%